Reconstructing Positive Self-Image among Juvenile Inmates through Positive Interactive Counselling: A Strength-Based Approach to Psychosocial Rehabilitation - Ababiel, Merinta Wira; Setyawan, Jefri; Elisabeth, Mary Philia (Utan Kayu Publishing, 2025)
This exploratory study examines how a brief Positive Interactive Counselling (PIC) session can foster positive self-image among justice-involved adolescents in an Indonesian juvenile correctional facility. Beyond a community outreach activity, the work is framed as qualitative descriptive research with a clear theoretical contribution to Positive Psychology and Psychosocial Rehabilitation. Three participants (ages 16–17), purposively sampled, completed a single 60-minute group session combining guided reflection and peer sharing. Data (fieldnotes, participant worksheets, and in-session reflections) were analyzed using reflexive thematic analysis. Three themes emerged: (1) a growing desire to make a positive impact coupled with personal responsibility; (2) recognition of self-potential linked to skills and long-term goals; and (3) spiritual strength as a stabilizing foundation in adversity. Empirically, the session elicited counter-stereotypic self-descriptions and visible peer affirmation; observed changes included increased self-confidence, self-awareness, and perceived readiness for social reintegration. Conceptually, findings illuminate how PIC may support self-reconstruction by aligning with autonomy, competence, and relatedness needs while normalizing hope and meaning-making in a culturally resonant setting. Practically, the study demonstrates a low-resource, replicable protocol suitable for constrained custodial contexts and points to directions for longitudinal and multi-site evaluation. Abstrak: Studi eksploratif ini menelaah bagaimana satu sesi singkat Positive Interactive Counselling (PIC) dapat membangun citra diri positif pada remaja binaan di sebuah lembaga pemasyarakatan anak di Indonesia. Melampaui kegiatan pengabdian masyarakat, penelitian ini diposisikan sebagai studi kualitatif deskriptif dengan kontribusi teoretis yang jelas terhadap Psikologi Positif dan Rehabilitasi Psikososial. Tiga partisipan (usia 16–17 tahun) yang dipilih secara purposif mengikuti satu sesi kelompok berdurasi 60 menit yang memadukan refleksi terarah dan peer sharing. Data (catatan lapangan, lembar kerja partisipan, dan refleksi selama sesi) dianalisis menggunakan reflexive thematic analysis. Tiga tema utama muncul: (1) meningkatnya keinginan memberi dampak positif yang disertai tanggung jawab pribadi; (2) pengenalan potensi diri yang terhubung dengan keterampilan dan tujuan jangka panjang; dan (3) kekuatan spiritual sebagai landasan stabil dalam menghadapi kesulitan. Secara empiris, sesi ini memunculkan deskripsi diri yang berlawanan dengan stigma serta afirmasi sejawat yang tampak; perubahan yang diamati meliputi peningkatan kepercayaan diri, kesadaran diri, dan kesiapan untuk reintegrasi sosial. Secara konseptual, temuan menunjukkan bahwa PIC dapat mendukung rekonstruksi diri dengan menyelaraskan kebutuhan otonomi, kompetensi, dan keterhubungan, sekaligus menormalisasi harapan dan pemaknaan dalam konteks budaya yang relevan. Secara praktis, studi ini mendemonstrasikan protokol berbiaya rendah yang dapat direplikasi di lingkungan pemasyarakatan yang terbatas, serta membuka arah evaluasi longitudinal dan multi-situs.